Role of pacemaking current in cardiac nodes: insights from a comparative study of sinoatrial node and atrioventricular node. - Liu, J; Noble, P; Xiao, G; Abdelrahman, M; Dobrzynski, H; Boyett, MR; Lei, M; Noble, D (2008)
Cardiac pacemaking in the sinoatrial (SA) node and atrioventricular (AV) node is generated by an interplay of many ionic currents, one of which is the funny pacemaker current (If). To understand the functional role of If in two different pacemakers, comparative studies of spontaneous activity and expression of the HCN channel in mouse SA node and AV node were performed. The intrinsic cycle length (CL) is 179+/-2.7 ms (n=5) in SA node and 258+/-18.7 ms (n=5) in AV node. Blocking of If current by 1 micromol/L ZD7288 increased the CL to 258+/-18.7 ms (n=5) and 447+/-92.4 ms (n=5) in SA node and AV node, respectively. However, the major HCN channel, HCN4 expressed at low level in the AV node compared to the SA node. To clarify the discrepancy between the functional importance of If and expression level of HCN4 channel, a SA node cell model was used. Increasing the If conductance resulted in decreasing in the CL in the model, which explains the high pacemaking rate and high expression of HCN channel in the SA node. Resistance to the blocking of If in the SA node might result from compensating effects from other currents (especially voltage sensitive currents) involved in pacemaking. The computer simulation shows that the difference in the intrinsic CL could explain the difference in response to If blocking in these two cardiac nodes.